POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN AKHLAK ANAK (Studi Kasus di Desa Bumi Pratama Mandira Kecamatan Sungai Menang Kabupaten Ogan Komering Ilir Sumatera Selatan) - Khoirul Hidayah Pratiwi; Eko Setiawan; Mutiara Sari Dewi (VICRATINA, 2022)
The most important parenting pattern is parenting. Parents are obliged to provide upbringing by instilling religious values since childhood, because children are like young plants whose character can still be formed during development. The parenting style applied in Bumi Pratama Mandira Village is very diverse, but has the same goal, which is to want their children to have good morals and understand religion. The method applied in providing parenting uses exemplary methods, advice, habits and punishments. This study uses a qualitative method where the data collection uses the method of observation, interviews and documentation and is supported by the opinions of experts. Each parent has a different parenting pattern from a diverse population. However, the success of parenting on the moral development and habituation of children at home has been considered quite good as evidenced by the children who often help their parents and are polite to their elder